Expert assessment of the effectiveness of the health and recreation program involving dragon boat racing for students - Liu , Jiale; Byshevets , Nataliia; Kovtun , Olha; Huba , Nataliia (Sportyvnyi Visnyk Prydniprovia, 2026)
Introduction. The implementation of new health-oriented programmes in the system of students’ physical education requires a thorough assessment of their methodological feasibility. The effectiveness of such programmes largely depends on the objectivity of expert evaluation, which makes it possible to identify strengths and potential areas for improvement prior to practical implementation. Particular attention is paid to dragon boat paddling as a means of promoting students’ physical and psycho-emotional development. Purpose. To theoretically substantiate and statistically confirm the effectiveness of a health-and-recreational dragon boat paddling programme for university students based on the analysis of qualified experts’ opinions. Methods. An expert panel (n = 25) consisting of physical education and sport professionals with different lengths of professional experience was involved in the evaluation. The programme was assessed using 23 indicators grouped into four criteria and rated on a 5-point Likert scale. Statistical analysis included the calculation of the arithmetic mean, standard deviation, coefficient of variation, and Kendall’s coefficient of concordance. Results. The analysis revealed a low level of agreement within the overall expert group due to heterogeneity of professional experience. The identification of a “competent core” (experts with more than 10 years of experience, n = 11) resulted in a substantial increase in the concordance coefficient (W = 0.561; p < 0.05). The highest ratings were obtained for outcome-related indicators, including improvement of psycho-emotional state, team interaction, and increased interest in physical activity. At the same time, areas for further development were identified, particularly the need to expand injury prevention exercises. Conclusions. The programme was statistically confirmed to be highly effective and ready for implementation, as mean scores across all criteria exceeded 4.0 points. The most objective results were obtained from the subgroup of experienced experts, characterized by high homogeneity of judgments (V < 14.74%). Priority directions for methodological refinement of the programme content were identified, primarily in the areas of special physical conditioning and injury prevention.